The clinical value of pathology tests and imaging study in the diagnosis of acute appendicitis. Issue 1092 (12th August 2016) - Chen, Ko-Chin; Arad, Alon; Chen, Ko-Chien; Storrar, Jonathan; Christy, Andrew G
Abstract: Objective: To explore the diagnostic accuracy of acute appendicitis among different patient groups and evaluate the statistical diagnostic values of common pathology and imaging tests for the diagnosis of acute appendicitis. Main Measures: Proportions of histology-proven appendicitis in different patient groups. Statistical parameters including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (+LR), negative likelihood ratio (-LR) and diagnostic odds ratio (DOR) between the histology-proven appendicitis and abnormal results of U/S, CT, WCC, CRP, bilirubin, pancreatic, and combined test results of WCC and CRP. Results: Our data showed that up to 25.7% of patients underwent appendectomy has normal appendix. Appendicitis is often accurately diagnosed among male patients, up to 90.3% of the time, while misdiagnosis of appendicitis among young females (<40 years old) is significantly high, up to 30.9%. CT has high diagnostic performance index for appendicitis, sensitivity > 90%, and no individual pathology test out of those examined can rival the sensitivity of CT. Nevertheless, by examining the combined results of WCC and CRP, we found that abnormal results in one or both these yields sensitivity similar to CT scans in detecting acute appendicitis, up to 95%. Conclusion: Young female patients have highest risk of being falsely diagnosed with acute appendicitis and hence unnecessary surgery. Bilirubin and lipase exhibit no correlations with acute appendicitis. Combined interpretation of WCC or CRP abnormal results yields competitive sensitivity as CT. Hencewe would suggest that, under the appropriate clinical context, one can use both WCC and CRP as a simple tool to support the diagnosis of appendicitis. If both tests show normal results, we would highly recommend considering alternative diagnosis.